Respuesta :
Answer:
if x = 2 , y = 1
if x = 5 , y = -5
Step-by-step explanation:
6(2) + 3y = 15
12 + 3y = 15
12 + 3(1) = 15
y = 1
6(5)+3(y) = 15
30 + 3(-5) = 15
30 - 15 = 15
y = (-5)
Answer:
1 and -5
Step-by-step explanation:
let's start with moving y to one side for convenience sake.
6x+3y=15
subtract 6x on both sides
3y=15-6x
divide by 3 on both sides
y=5-2x
all you have to do is replace x with whatever number you want it to equal. starting with 2:
y=5-2(2)=5-4=1
now let's replace x with 5
y=5-2(5)=5-10=-5